2013
DOI: 10.1364/oe.21.006509
|View full text |Cite
|
Sign up to set email alerts
|

Selective photodeposition of zinc nanoparticles on the core of a single-mode optical fiber

Abstract: An experimental and theoretical study about selective photodeposition of metallic zinc nanoparticles onto an optical fiber end is presented. It is well known that metallic nanoparticles possess a high absorption coefficient and therefore trapping and manipulation is more challenging than dielectric particles. Here, we demonstrate a novel trapping mechanism that involves laser-induced convection flow (due to heat transfer from the zinc particles) that partially compensates both absorption and scattering forces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…The size of the cone depends directly on the time that the optical fiber is submerged in the acid solution, we have found that cones 25 µm wide and 20 µm deep are suitable for this application. The incorporation of nanoparticles on the surfaces of the etched cone was carried out using the technique known as photodeposition [2,11,14]. Toner micro particles were used in the experiment, the particles without dissolving have a size between 3 and 30 m, after being dissolved their sizes range between 70 and 700 nm [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the cone depends directly on the time that the optical fiber is submerged in the acid solution, we have found that cones 25 µm wide and 20 µm deep are suitable for this application. The incorporation of nanoparticles on the surfaces of the etched cone was carried out using the technique known as photodeposition [2,11,14]. Toner micro particles were used in the experiment, the particles without dissolving have a size between 3 and 30 m, after being dissolved their sizes range between 70 and 700 nm [17].…”
Section: Methodsmentioning
confidence: 99%
“…It consists in a hybrid structure (solid / liquid / gas) generated by heating the tip of the fiber by the guided light and it can be regenerated with low cost and good performance. The thermal effect is achieved by absorption of light in micro or nanoparticles deposited on the fiber tip; gold, silver or zinc have been used as absorbers [2,11,[14][15], the absorber is usually heated at a pump wavelength of 980 nm [11,13]. The heat evaporates spherical bubbles which undergo deformations due to physical or chemical phenomena produced in the liquid where they are formed, these deformations are detected a probe laser at a typical wavelength of 1550 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Explorer 532-200-E) is coupled into a multimode optical fiber (OF G , 50/125 µm), using an aspherical lens with a focal distance of 4.5 mm as shown in Figure 1. Previously, AgNPs were immobilized using the photodeposition technique at the distal end of the fiber OF G [21][22][23]. The optical power loss caused by AgNPs absorption was approximately 2 dB.…”
Section: Methodsmentioning
confidence: 99%
“…In previous works [19], we have realized a theoretical and experimental study about this technique by means of zinc nanoparticles and laser light which travels into a single-mode optical fiber. The origin of the technique is based on the radiation pressure of laser light (absorption and scattering forces) and the force is achieved by particles moving in convection currents (Stokes force) which are provoked by the strong absorption photons in the metal nanoparticles.…”
Section: Methodsmentioning
confidence: 99%
“…Particles close to the core of the optical fiber end are adhered to it. This phenomen is produced by particle interactions through a double layer repulsion and London attraction force [19,20]. With this method is possible to choose the maximum size of nanoparticles adhered on the optical fiber end by means of the laser power.…”
Section: Methodsmentioning
confidence: 99%